completing the square math homework help

Get perfect grades by consistently using www.assignmentgeeks.org. Place your order and get a quality paper today. Take advantage of our current 20% discount by using the coupon code GET20


Order a Similar Paper Order a Different Paper

—————————————————————————————————-

Solve the equation by completing the square.

x2 ­- 10x + 28 = 0


a. x ≈ 3.3, x ≈ 6.7

b. x = 5 + i√3, x = 5 − i√3

c. x ≈ 18.5, x ≈ 1.5

d. x = 10 + i√3 , x = 10 − i√3

==========================================

Rewrite the equation so that the left side is a factored perfect square.

3×2 ­ – 4x = 2

======================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

x2 + 8x + 9 = – ­9


a. x2 + 8x + 16 = 16

b. x2 + 8x + 16 =- ­2

c. x2 + 8x + 64 = 46

d. x2 + 8x + 64 = 64

==============================================

Find the value of c that will make the expression a perfect square trinomial.

x2 + 0.6x + c


a. 0.3

b. 0.36

c. 0.9

d. 0.09

==============================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

A. 2 x squared space plus space 3 x space plus space 9 over 4 equals 29 over 4
B. x squared space plus space 3 over 2 x space plus space 9 over 16 equals 49 over 16
C. x squared space plus space 3 over 2 x space plus space 9 over 4 space equals space 29 over 4
D. x squared space plus space 3 over 2 x space plus space 9 over 16 equals negative 71 over 16

================================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

x2 ­ – 4x + 1 = 0


­a. x2 – 4x + 4 = -3

b. x2 – ­ 4x + 5 = 0

c. x2 ­- 4x + 4 = ­3

d. x2 ­- 4x + 4 = ­5

======================================

Find the value of c that will make the expression a perfect square trinomial.

x2 ­- 15x + c


a. -7.5

b. 7.5

c. -56.25

d. 56.25

================================================

Rewrite the equation by factoring the perfect square trinomial.

x2 + 8x + 16 = 7


a. (x + 4)2 = 7

b. (x – ­ 4)2 = 7

c. (x + 8)2 = 7

d. (x ­ – 8)2 = 7

==============================================

Rewrite the equation by factoring the perfect square trinomial.

x2 + 12x + 36 = 25


a. (x ­- 6)2 = 5

b. (x ­- 6)2 = 25

c. (x + 6)2 = 25

d. (x + 6)2 = 5

Writerbay.net

Do you need help with this or a different assignment? We offer CONFIDENTIAL, ORIGINAL (Turnitin/LopesWrite/SafeAssign checks), and PRIVATE services using latest (within 5 years) peer-reviewed articles. Kindly click on ORDER NOW to receive an A++ paper from our masters- and PhD writers.

Get a 15% discount on your order using the following coupon code SAVE15


Order a Similar Paper Order a Different Paper